2020
DOI: 10.1007/s00411-020-00861-y
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need the “detriment” for radiation protection?

Abstract: The purpose of the ICRP detriment concept is to enable a quantitative comparison of stochastic radiation damage for the various organs. For this purpose, the organ-specific nominal risk coefficients are weighted with a function that is intended to express the amount of damage or, respectively, the severity of a disease. This function incorporates a variety of variables that do not depend on radiation parameters, but on characteristics of the disease itself. The question is raised as to whether the rather subtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Applying the same methodology, with risk models based on the LSS, Walsh et al (2019) demonstrated how reference dose levels translated differently into specific cancer risk levels depending on age at exposure, gender, time since exposure, and type of cancer within the German population. ICRP is also planning new recommendations that may well include new parameters (Cléro et al 2019, Zhang et al 2020) which would need more transparency and comprehensibility for non-specialists in radiation protection (Breckow 2020). This growing trend on improving the understanding and the estimate of health consequences could help to get broader types of results than effective doses by the use of alternative quantities such as lifetime excess cancer risk for the most sensitive organ.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the same methodology, with risk models based on the LSS, Walsh et al (2019) demonstrated how reference dose levels translated differently into specific cancer risk levels depending on age at exposure, gender, time since exposure, and type of cancer within the German population. ICRP is also planning new recommendations that may well include new parameters (Cléro et al 2019, Zhang et al 2020) which would need more transparency and comprehensibility for non-specialists in radiation protection (Breckow 2020). This growing trend on improving the understanding and the estimate of health consequences could help to get broader types of results than effective doses by the use of alternative quantities such as lifetime excess cancer risk for the most sensitive organ.…”
Section: Discussionmentioning
confidence: 99%
“…The proposal deserves special attention because DALY is intuitive and easy to communicate, focuses on the quality of life rather than on a generic risk that can occur at any time in life, and places radiological risk in a context with other risks. DALY was already proposed as a metric of radiation health risk [48], and the authors suggested that it is superior to the concept of "detriment" used by ICRP [49]. Of course, DALY still requires the data used in REID, RADS, or LCM metrics.…”
Section: Csamentioning
confidence: 99%
“…In Publication 103 (ICRP, 2007), incidence-based cancer risk models were introduced, and the basis of estimating the risk of heritable disease was revised based on updated knowledge of human genetic diseases and the process of germline mutagenesis. These modifications are considered reasonable, and changes in the estimated values reflect scientific understanding and data available at the time. (114) Despite efforts to assess the non-fatal component, fatal cancer risk accounts for a substantial fraction of radiation detriment (Breckow, 2020). This is because cancer constitutes a major part of stochastic effects, and the current scheme of severity adjustment relies mainly on the lethality fraction.…”
Section: Potential Evolutionmentioning
confidence: 99%
“…(114) Despite efforts to assess the non-fatal component, fatal cancer risk accounts for a substantial fraction of radiation detriment (Breckow, 2020). This is because cancer constitutes a major part of stochastic effects, and the current scheme of severity adjustment relies mainly on the lethality fraction.…”
Section: Potential Evolutionmentioning
confidence: 99%